Peningkatan Pembelajaran Iqro’ di SLB Tuna Rungu Sukarame Bandar Lampung melalui Quantum Learning - wahyudi, Imam; hariyanto, Jimy (Universitas Islam Negeri Raden Intan Lampung, 2017)
This study aims to find out the Iqro learning process using the Quantum Learning method and find out the effectiveness of the Quantum Learning method to improve the learning achievement of class V students of the PKK SLB Lampung Province. This research is a Classroom Action Research (CAR) or classroom action research conducted in the classroom when the learning process takes place, in the process of its application, this research consists of several cycles and stages. This study consisted of three cycles of 5 students, consisting of 2 female students and 3 students. Each cycle consists of four stages, namely plan (planning), act (action), observe (observation), and reflect (reflection). While data collection is done by observation, interviews, and documentation. Inductive, deductive, and TDF statistical analysis. The results of this study indicate: Iqro learning process using the Quantum Learning method can take place well in three cycles and is carried out in 6 stages, namely fostering student attitudes, getting used to reading, getting used to writing, structuring the learning environment, training children's memory, training children to learn creatively . From this stage, the aim is to invite students to learn actively, dynamically, communicatively and happily. So that the learning process is not felt as formal saturating space. In another aspect, the application of methods in presenting student learning evacuation as something that seems interesting and challenging. With the application of the Quantum Learning method can help teachers in fixing the weaknesses of teaching and student learning, namely simplification of theory into mind mapping (concept map ) so the learning material is easy to remember. Besides that, this method can also be applied to language learning and other subject areas.